Analysis of Physical Status Indicators of Primary School Students - Khankeldiev Sh.X.; Akhmadaliev Sh. (Zien Journals, 2022)
This article analyzes the indicators of physical development and physical fitness of primary school students. Indicators of physical development and physical fitness of students were also developed by innovative methods.
Keywords: Physical status; indicators of physical development and physical fitness; innovations; methods